If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5m+8=-4m+3
We move all terms to the left:
-5m+8-(-4m+3)=0
We get rid of parentheses
-5m+4m-3+8=0
We add all the numbers together, and all the variables
-1m+5=0
We move all terms containing m to the left, all other terms to the right
-m=-5
m=-5/-1
m=+5
| (2x–8)(x+7)=0 | | x=-7+1/3 | | 2x–8)(x+7)=0 | | 5/2v+4=4/5v-3/5 | | 13+3h=82 | | -(n+1)-5(3-n)=1+n+1-3n* | | 4+p/4=-1 | | 3x+11=-11 | | 10b-76=6b | | 82=w+34 | | (x^2)+x+18=90 | | 9b+6=-102 | | 82=u+26 | | -6(b-7)=90* | | 11+3x=-11 | | 3/4x+24=36-1/4x | | n-3n=12* | | 0.1=10^x | | 11a-67=5a-7 | | -11=3x+11 | | 11a–67=5a-7 | | 6-(21/3-1.5)=q | | 5u+95=9u+11 | | 15-8x+2=10-3(2x-4) | | 1/2x+60=120-1/4x | | 2w-32=4w-92 | | 3y/6-1=1 | | -3n+3(4n+15)=-21+17 | | -2z+z=-z | | 2x+62=3x+57 | | 3x/4-5/7=2x | | 8b=b+28 |